Comparative efficacy studies of nine Chinese traditional patent medicines for the treatment of post-myocardial infarction heart failure: A Bayesian network - Fuyun Jia; Shengwei Gao; Qiaochu Zhu; Opoku Bonsu Francis; Rui Liu; Yadong Wang; Rui Zhang; Shichuan Chen; Zilian Zhan; Xi Zhang; Qiang Xu (Pharmacological Research - Modern Chinese Medicine)
Introduction: Heart failure (HF) is a rapidly growing public health issue with an estimated prevalence of 64 million people globally. After many years of use and development, Traditional Chinese Medicine (TCM) has accumulated rich clinical usefulness in many diseases. This network meta-analysis aimed to assess the effectiveness of nine different Chinese traditional patent medicines (CTPMs) in the treatment of heart failure developing after acute myocardial infarction. Methods: Determine the eligibility criteria for inclusion and exclusion in advance. Starting from literature search until September 20, 2024, conduct comprehensive data retrieval on 7 different databases. Network plots, league tables, surface-under-the-cumulative ranking (SUCRA), and funnel plots were created for each outcome. A previous registration (PROSPERO CRD42024519394) of this review protocol was undertaken. Results: A total of 56 eligible RCTs involving 5,567 patients with heart failure secondary to acute myocardial infarction in which nine CTPMs were used as treatment are included. The CTPMs included Qili Qiangxin capsule (QLQXC), Compound Danshen Dripping Pills (CDDP), Shexiang Baoxin pill (SXBXP), Stilbene yiqi dropping refs (SYQDR), Xintong oral liquid (XTOL), Wenxin granule (WXG), Tongxinluo capsule (TXLC), and Guanxinshutong capsule (GXSTC) and Huangqibaoxin particle (HQBXP). The experimental group received CTPM therapy in addition to conventional Western medicine (CWM) treatment, whereas the control group received just CWM treatment. The results showed that compared to those treated with CWM alone, those treated with CPTM + CWM considerably improved in all relevant measures. When evaluating clinical effectiveness based on left ventricular end-diastolic diameter and the New York Heart Association's (NYHA) cardiac functional classification, WXG + CWM was shown to be the most successful in enhancing cardiac efficiency. The 6-minute walking test results were most improved by SXBXP + CWM, but N-terminal pro-brain natriuretic peptide reduction, left ventricular ejection percent, and left ventricular end-systolic diameter were best achieved by XTOL + CWM. When compared to the other combination treatments, the QLQXC + CWM therapy was the most successful in increasing left ventricular end-diastolic volume while the GXSTC + CWM treatment was the most successful in increasing left ventricular end-systolic volume. There were no appreciable variations in safety between the groups treated with CWM alone and the ones treated with CTPMs plus CWM. Discussion: In contrast to CWM therapy alone, the combination of CTPMs and CWM treatment offers greater therapeutic benefits and is safe for treating heart failure that follows an acute myocardial infarction. For heart failure that develops after an acute myocardial infarction, combo therapy using WXG + CWM and QLQXC + CWM may be the best integrative medicine-based interventions. Due to the study's limitations, additional large-scale, multicenter, double-blind, randomized controlled trials with high quality are required for comprehensive validation and to establish a solid body of evidence supporting the prudent use of medications in the treatment of heart failure resulting from acute myocardial infarction.